ANALISIS PENERAPAN ELEKTRONIC DATA PROCESSING TERHADAP PENGAWASAN PERSEDIAAN PADA PT. MAKMUR SEJAHTERA MEDAN - Safitri, Nabila; Rozi, Facrul; Suhariyanti, Suhariyanti (Worksheet : Jurnal Akuntansi, 2024)
The increasing demand for accuracy and efficiency in inventory management has driven companies to adopt advanced technological solutions such as Electronic Data Processing (EDP) systems. This study examines the implementation of EDP in inventory supervision at PT. Makmur Sejahtera Medan, which faces challenges related to operator competency and system optimization. The research adopts a qualitative descriptive approach, incorporating in-depth interviews, direct observation, and document analysis to understand the current state of EDP application and identify obstacles. The findings reveal that while the integration of the Si Log system has enhanced data processing and inventory tracking, limitations persist due to inadequate operator training and the absence of a robust backup system. These challenges hinder the full potential of EDP systems in achieving seamless inventory management. The study implies that targeted training programs and the development of contingency systems are essential for optimizing EDP implementation and ensuring data accuracy and operational continuity. The results contribute to the body of knowledge on EDP adoption in medium-sized enterprises, highlighting both successes and areas needing improvement to guide future technological strategies.